2016
DOI: 10.1103/physrevapplied.6.044023
|View full text |Cite
|
Sign up to set email alerts
|

Injection Locking of Quantum-Dot Microlasers Operating in the Few-Photon Regime

Abstract: We experimentally and theoretically investigate injection locking of quantum dot (QD) microlasers in the regime of cavity quantum electrodynamics (CQED). We observe frequency locking and phase-locking where cavity enhanced spontaneous emission enables simultaneous stable oscillation at the master frequency and at the solitary frequency of the slave microlaser. Measurements of the second-order autocorrelation function prove this simultaneous presence of both master and slave-like emission, where the former has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…Analog to previous studies, no pronounced change in threshold current as well as no hysteresis of output intensity between the increase and decrease of the excitation current can be observed. These effects are masked by the high spontaneous emission noise which smooths out the gain clamping at laser threshold [13].…”
Section: Tailoring the Microlaser Properties With Delayed Optical Feementioning
confidence: 99%
See 1 more Smart Citation
“…Analog to previous studies, no pronounced change in threshold current as well as no hysteresis of output intensity between the increase and decrease of the excitation current can be observed. These effects are masked by the high spontaneous emission noise which smooths out the gain clamping at laser threshold [13].…”
Section: Tailoring the Microlaser Properties With Delayed Optical Feementioning
confidence: 99%
“…Particularly, lasing has been demonstrated in the single-QD regime [7] paving the way towards the limiting case of thresholdless lasing [8][9][10][11][12]. From the standpoint of nonlinear laser dynamics, high-β QD micropillar lasers show particular dynamical regimes not present in standard large-scale semiconductor lasers like partial injection locking [13]. Moreover, intrinsically nonlinear switching dynamics result from the gain-competition between the two…”
mentioning
confidence: 99%
“…In contrast, the above-threshold weak mode linewidth increases, which indicates a non-complete transition to laser action for this mode. Previous injectionlocking experiments in QD-micropillar lasers showed that a locking range of around 1 GHz [40] can be expected. In order to be able to resolve possible locking effects between the two microlasers, linewidths smaller than the expected locking range and hence output powers of at least 30 nW are required (see Fig.…”
Section: Methodsmentioning
confidence: 96%
“…Synchronisation has been studied in a wide range of classical systems [2], as well as in systems such as lasers where semiclassical descriptions prove accurate [3,4]. Over the last few years experiments have begun to investigate synchronisation in smaller-scale oscillator systems, including micron-sized mechanical oscillators [5][6][7][8] and lasers operating in the few-photon regime [9]. Recently, theorists have also started to explore synchronisation in oscillators where a fully quantum mechanical description becomes essential [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%